Effect of Silver Nano-particles on Tensile Strength of Acrylic Resins - Tahereh Ghaffari; Fahimeh Hamedi-rad (Tabriz University of Medical Sciences, 2015)
Background and aims. Polymethyl methacrylate (PMMA) is widely used for the fabrication of removable prostheses. Silver nano-particles (AgNps) have been added to PMMA because of their antimicrobial properties, but their effect on the mechanical properties of PMMA is unknown. Theaim of this study was to investigate the effects of AgNps on the tensile strength of PMMA. Materials and methods. For this study, 12 specimens were prepared and divided into two groups. Group 1 included PMMA without AgNps and group 2 included PMMA mixed with 5 wt% of AgNps. Tensile strength of the specimens was measured by Zwick Z100 apparatus. Statistical analysis was carried out by SPSS using t-test. Statistical significance was defined at P<0.05. Results. This study showed that the mean tensile strengthof PMMA in group 2 was significantly lower than that in group 1. Therefore, the tensile strength decreased significantly after incorporation of silver nano-particles. Conclusion. Within the limitations of this study, tensile strength of acrylic resin specimens was influenced by silver nano-particles.